Improving the job shop scheduling algorithm to minimize total penalty costs considering maintenance activity - Puryani, Puryani; Chalida, Nurmalia; Soepardi, Apriani; Chaeron, Mochammad; Nafisah, Laila (OPSI, 2024)
Production scheduling is generally based on the assumption that resources are always available. In reality, these resources, machines, and supporting facilities experience limited availability due to interruptions during the production process. Therefore, to improve these conditions, the maintenance process conducted to reduce the disruption level of the machine needs to be scheduled as part of the available for job processing leading to penalty costs, such as tardiness and earliness. This research aims to develop a new algorithm to solve job shop scheduling problems to minimize the total penalty cost by considering machine unavailability due to scheduled maintenance activities. The proposed model modifies the existing model using a combination of priority rules and a heuristic approach algorithm known as priority dispatching. The result showed that the proposed model produces a greater total cost with a larger flow time than the previous model. Although the flow time is larger, it is more realistic according to real conditions because the proposed model considers machine maintenance activities. Furthermore, the combination of priority rules used also affected the flow time and the total penalty costs incurred, which can be minimized through several alternatives.